2021
DOI: 10.3390/molecules26010228
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wound-Healing and Antioxidant Effects of Marantodes pumilum (Blume) Kuntze in an Excision Wound Model

Abstract: Marantodes pumilum (MP) is a great source of herbal medicine used traditionally by both men and women for various purposes. MP may have potential wound-healing effects due to its diverse biological properties. An extensive study was conducted in a normal male rat model for determining the effects of MP var. pumila (MPvp) and var. alata (MPva) on the wound healing process. Here, 126 male Sprague-Dawley rats were divided randomly into seven groups as follows: sham-operated (SH), vehicle dressing (VD), flavine dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The antioxidant activity contributing towards wound healing is in accordance with previous studies reporting enhanced wound healing due to potent antioxidant activities [92]. LP significantly increased in the negative control group (p < 0.0001) compared to the intact group, which accords with previously recorded data [93]. No significant differences in LP were observed in treatment groups with either ArJ or SS groups compared to the negative control, while the ArJ and SS treated groups exhibited significant increases (p < 0.0001) compared to the intact group (Table 5).…”
Section: Role Of Antioxidants and Oxidative Stress Markers In Wound H...supporting
confidence: 92%
“…The antioxidant activity contributing towards wound healing is in accordance with previous studies reporting enhanced wound healing due to potent antioxidant activities [92]. LP significantly increased in the negative control group (p < 0.0001) compared to the intact group, which accords with previously recorded data [93]. No significant differences in LP were observed in treatment groups with either ArJ or SS groups compared to the negative control, while the ArJ and SS treated groups exhibited significant increases (p < 0.0001) compared to the intact group (Table 5).…”
Section: Role Of Antioxidants and Oxidative Stress Markers In Wound H...supporting
confidence: 92%
“…Wound healing is thus a complicated process that can be affected by several factors including infection, stress, contamination, medication, and sex hormones. Recently, many medications have become available on the world market to treat/heal wounds 21 . However, these treatments exhibit limitations based on cost, treatment time, and toxicity (side effects).…”
Section: Introductionmentioning
confidence: 99%
“…Various wound healing agents, including anti-inflammatories and antioxidant free radical scavengers, have been reported 21 , 22 . Curcumin or curcuma longa is a plant commonly used as a culinary ingredient but which also exhibits potent antioxidant, antiseptic, anti-inflammatory, blood purifying, and wound-healing agent properties 23 .…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the active compounds in the ethanolic extract of D. ochreata leaves could increase the epithelialization process, thus accelerating the wound healing process. Epithelial formation begins during the transitional phase, after the inflammatory phase, and before the proliferative phase (Ahmad et al, 2021). In this transitional phase, inflammatory mediators are still released on the burned skin, so epithelialization has not occurred correctly (Tiwari, 2012).…”
Section: Discussionmentioning
confidence: 99%